2017
DOI: 10.1186/s12967-017-1250-4
|View full text |Cite
|
Sign up to set email alerts
|

CSPG4: a prototype oncoantigen for translational immunotherapy studies

Abstract: Thanks to striking progress in both the understanding of anti-tumor immune response and the characterization of several tumor associated antigens (TAA), a more rational design and more sophisticated strategies for anti-tumor vaccination have been possible. However, the effectiveness of cancer vaccines in clinical trial is still partial, indicating that additional studies are needed to optimize their design and their pre-clinical testing. Indeed, anti-tumor vaccination success relies on the choice of the best T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 122 publications
(140 reference statements)
0
102
0
Order By: Relevance
“…Early strategies targeting CSPG4 utilized the development of anti-idiotypic antibodies (anti-id), which target the binding sites of other anti-CSPG4 antibodies, essentially mimicking the tumor antigen’s binding site on the antibody, and thus aiming to serve as immunogens or vaccines ( 91 , 92 ). A clinical study reported increased survival and metastasis regression in patients with melanoma who developed anti-CSPG4 antibodies following administration of the anti-idiotypic mAb MK2-23 ( 93 ).…”
Section: Cspg4 As a Target For Antibody Therapies In Cancermentioning
confidence: 99%
“…Early strategies targeting CSPG4 utilized the development of anti-idiotypic antibodies (anti-id), which target the binding sites of other anti-CSPG4 antibodies, essentially mimicking the tumor antigen’s binding site on the antibody, and thus aiming to serve as immunogens or vaccines ( 91 , 92 ). A clinical study reported increased survival and metastasis regression in patients with melanoma who developed anti-CSPG4 antibodies following administration of the anti-idiotypic mAb MK2-23 ( 93 ).…”
Section: Cspg4 As a Target For Antibody Therapies In Cancermentioning
confidence: 99%
“…Systemic chemotherapy has yielded controversial and quite disappointing results and recently, attention has been focused on the role of the immune system resulting in the development of two immunotherapeutic approaches, namely a xenogeneic DNA vaccine against human tyrosinase (Oncept, Merial), and a CSPG4-immunotargeting vaccine. 1 Despite a significant improvement in treatment during the last years, canine MM continues to represent a major clinical challenge.…”
Section: Funding Information Nouscom Srlmentioning
confidence: 99%
“…Regardless of the anatomical location, complete surgical resection associated with regional lymphadenectomy and/or radiotherapy is the preferred treatment modality. Systemic chemotherapy has yielded controversial and quite disappointing results and recently, attention has been focused on the role of the immune system resulting in the development of two immunotherapeutic approaches, namely a xenogeneic DNA vaccine against human tyrosinase (Oncept, Merial), and a CSPG4‐immunotargeting vaccine …”
Section: Introductionmentioning
confidence: 99%
“…As a step in this direction, we focused our attention on one of the most interesting MAA identified so far, the chondroitin sulfate proteoglycan 4 (CSPG4). It is a prototype “oncoantigen” in human melanomas, since it has a restricted expression in healthy/normal tissues, but a high expression on melanoma cells in almost 85% of patients [ 150 , 151 ]. The CSPG4 has a key role in regulating the proliferative, migratory, invasive and metastatizing ability of cancer cells and their chemoresistance, therefore simultaneously regulating several processes needed for cancer development and progression.…”
Section: The Dog Revolution: Canine Tumors As Pre-clinical Models mentioning
confidence: 99%
“…On these bases, we identified CSPG4 as a new marker for canine patients affected by spontaneous oral melanoma [ 151 , 152 ]. We performed two veterinary trials to evaluate the potential of a xenogeneic DNA vaccine coding for the human CSPG4 in canine melanoma patients affected by spontaneous stage II-III CSPG4-positive oral melanomas.…”
Section: The Dog Revolution: Canine Tumors As Pre-clinical Models mentioning
confidence: 99%